Stress Management in Service Sector - Seethanaik, D. (International Research Journal of Management, IT & Social Sciences, 2015)
This paper describes the causes stress in the hospital. The paper examines the techniques or methods used to lower stress. The paper examines various stress reduction techniques to alleviate stress. This paper is to identify emotional, physical and mental effects of stress. Also this paper explores work related sources of stress.